Correlation between apolipoprotein B and endothelin-1-induced vasoconstriction in humans - Romerio, Silvana C.; Linder-Schönenberger, Lilly; Flammer, Josef; Haefeli, Walter E. (Peptides, 2000)
Low-density lipoprotein (LDL) concentrations have been linked to altered responses to endogenous vasodilators and vasoconstrictors. We evaluated retrospectively the relationship between LDL and vasoconstrictor (endothelin-1, phenylephrine) responsiveness of the forearm vasculature in 15 elderly healthy volunteers with apolipoprotein B and LDL levels in the normal range. In contrast to phenylephrine, changes in forearm vascular resistance induced by endothelin-1 were correlated with apolipoprotein B, LDL, and total cholesterol concentrations in women but not in men. These findings might suggest that lipids may increase vascular tone through both impaired endothelial vasodilation and increased vasoconstriction to endothelin-1 at least in women.
Gesehen am 27.05.2021